If You've Got Leavin' on Your Mind: The Identification and Validation of Pre-Quitting Behaviors. (November 2018) - Gardner, Timothy M.; Van Iddekinge, Chad H.; Hom, Peter W.
This study introduces the concept of pre-quitting behaviors (PQBs), which employees in the process of leaving an organization may unknowingly "leak" and others can observe and use to identify those at risk of turnover. We develop a theoretical framework that explains how and why turnover proclivity can be encoded into observable PQBs. Then, on the basis of input from employees who voluntarily left and their managers, we identify a range of PQBs that served as the basis for an initial measure of the behaviors. Analysis of data to assess the validity of inferences based on the measure revealed that PQBs predicted future voluntary turnover over and above established antecedents of this outcome. Overall, this study suggests that the psychological and behavioral processes that activate and facilitate voluntary turnover are manifest in observable behaviors and thus opens a new line of inquiry into the process of employee turnover.